Aplikasi Pupuk Urea pada Pertumbuhan Bibit Jabon Merah (Anthocephalus macrophyllus (Roxb.) Havil) di Persemaian (Studi Kasus di IUPHHK PT.Telagabakti Persada Halmahera Selatan) - Laswi Irmayanti; Nurmaya Talib; Salam Salam (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Red Jabon (Anthocephalus macrophyllus (Roxb.) Havil.) is one of the fast growing species that became priority to be developed in South Halmahera Regency, North Maluku Province. Currently the red jabon has become “Local Superior Crops” in North Maluku. One of IUPHHK in South Halmahera which develops red jabon is PT. Telagabakti Persada. The purpose of this study was to determine the best growth of red jabon seedling on urea fertilizer application. The study was conducted at PT. Telagabakti Persada, South Halmahera. The treatments of urea fertilizer were 0 g, 0.25 g, 0.50 g, 0.75 g, and 1 g. The results showed that the urea 0.25 g fertilizer treatment resulted in the best growth of red jabon seedlings.Key words: Red Jabon, Nursery, Growth of seedling, Urea